Echocardiographic parameters predicting spontaneous closure of ductus arteriosus in preterm infants - He, Minyu; Yang, Zhengchun; Gan, Tian; Tang, Jing; Ran, Suzhen; Zhang, Kun (Frontiers in Pediatrics, 2023)
Objective： To evaluate the value of echocardiographic parameters in predicting early spontaneous closure of ductus arteriosus in premature infants. Methods： 222 premature infants admitted to the neonatal ward of our hospital were selected, which patent ductus arteriosus was detected by echocardiography 48 hours after birth. On the 7th day, whether the ductus arteriosus was closed naturally in this cohort was observed. The infants whose ductus arteriosus were not closed were identified as the PDA group (n = 109), and the other infants were included in the control group (n=113). The echocardiographic parameters of the two groups of premature infants at 48 hours after birth were statistically analyzed, and the parameters with statistically significant differences were selected for multivariate logistic stepwise regression analysis. Results： The ductus arteriosus shunt velocity and the pressure difference between the descending aorta and the pulmonary artery (△Ps) in the PDA group were lower than those in the control group (P<0.05). The pulmonary artery pressure (PASP) in the PDA group was higher than that in the control group(P<0.05). According to the multivariate logistic stepwise regression analysis, only the maximum shunt velocity of ductus arteriosus was correlated with early spontaneous closure of ductus arteriosus in 48h first echocardiographic parameters(P=0.049). Conclusion： Echocardiographic parameters are of great value in predicting the early spontaneous closure of ductus arteriosus in premature infants. In particular, the ductus arteriosus shunt velocity is correlated with the early spontaneous closure of ductus arteriosus.